The Insulin: Glucagon Ratio and Obesity - Kalra, Sanjay; Arora, Saurabh; Kapoor, Nitin (Journal of the Pakistan Medical Association, 2023)
This communication discusses the physiology and pathology of the insulin glucagon ratio, with respect to obesity. Though high insulin levels are associated with obesity in this manuscript the authors specifically highlight its role in the causation and clinical management of obesity. It suggests that the term insulin glucagon ratio be used in preference to glucagon insulin ratio, and shares insights which may be helpful in informing future research. Keywords: Diabetes, overweight, obesity, metabolic fulcrum, metabolic seesaw, ominous octet of obesity